Fashion Branding: Upaya Diferensiasi Produk dan Unique Selling Point Merek Bertjorak - Arinda, Syafa; Lubis, Evawani Elisa; Rimayanti, Nita (Jurnal Riset Komunikasi (JURKOM), 2025)
This research discusses branding strategies and Unique Selling Points (USP) as important elements in forming the Bertjorak brand image, which is inspired by Indonesian culture through a combination of eccentric colors in its products. Using qualitative methods, this research collects data through interviews, observation and documentation. The research results show that Bertjorak successfully implemented a co-branding strategy through collaboration with singer Basboi in the project "Knitnote: Thread of Tunes," which not only promotes products but also combines artistic and creative values. This collaboration strengthens brand awareness and equity, and increases sales. In addition, Bertjorak stands out with continuous innovation, including empowering PKK mothers through sewing training, which helps improve skills and strengthen community ties. Despite facing challenges such as changing fashion trends and limited human resources, Bertjorak has managed to stay relevant and expand its market through adaptation and deep understanding of consumer preferences.